A inovação como recurso na internacionalização de empresas brasileiras: o caso do revólver The Judge no mercado norteamericano - Azambuja, André Luís Volkmann (Universidade do Vale do Rio dos Sinos, 2015)
This work aimed to evaluate the product innovation as a resource in internationalization of Brazilian companies and how the product innovation was employed as a strategic resource, through the lens of Resource Based View, in the internationalization of a Forjas Taurus S.A. company. Conceptual models of innovation, companies’ internationalization and Resource Based View were used to this end. Therefore, the intention was to discuss the role of innovation as resource for the generation of knowledge and learning during the process of internationalization. To achieve this purpose, it was investigated the innovation as resource into the business internationalization process, through a case study in the company Forjas Taurus S.A., whose focus was to evaluate whether the introduction of Judge revolver’s internationalization process created competitive advantage in the US market. The dissertation was established through a descriptive, single and qualitative case study. The data collection was carried out through documental analysis, direct observation and in-depth interviews with managers who have had involvement in the developing and introduction process of The Judge revolver, in the north-American market. According to the analysis, it was found that the possibility of exploring the north-American market with an innovative product was essential in its internationalization process to the United States. It was also identified that product innovation was the main strategic resource in the internationalization process of The Judge. In addition, it became clear that The Judge revolver attested been, from the point of view of RBV, a valuable, rare, inimitable and irreplaceable product, generating competitive advantage in the US market.
Keywords: Visão baseada em recursos; Processo de internacionalização; Inovação; Taurus; Indústria bélica brasileira; Resource based view; Internationalization; Innovation; Taurus; Brazilian defense industry; ACCNPQ::Ciências Sociais Aplicadas::Administração